Subcritical fluid and molecular distillation extraction of Nannochloropsis gaditana lipid and its metabolic benefits in hyperlipidemic mice - Meng, Ruilong; Zhang, Yu; Jiang, Yishan; Li, Bin; Chen, Xi; Sun, Zhongliang; Sun, Liqin (Frontiers in Nutrition, 2025)
The marine microalga Nannochloropsis gaditana is a fast-growing species rich in long-chain polyunsaturated fatty acids (PUFAs), particularly eicosapentaenoic acid (EPA), and other bioactive compounds. In this study, lipids from N. gaditana powder were extracted and refined using subcritical butane combined with molecular distillation to obtain a highly purified lipid extract with increased EPA concentration (58.92% w/w) and improved biological activity. The anti-hyperlipidemic effects of the lipid extract were evaluated in female Kunming mice (4 weeks old) fed a high-fat diet. Results demonstrated that N. gaditana lipid supplementation significantly reduced body weight gain, serum triglycerides (TG), total cholesterol (TC), and low-density lipoprotein cholesterol (LDL-C), while elevating high-density lipoprotein cholesterol (HDL-C). Additionally, the lipid extract ameliorated hepatic inflammation (reduced TNF-α and IL-1β levels), attenuated oxidative stress (enhanced SOD, CAT, and GSH-Px activities), and modulated lipid metabolism enzymes (inhibited FAS, ACC, and HMGCR; upregulated LCAT). These findings highlight the potential of EPA-rich N. gaditana lipid as a natural and sustainable therapeutic strategy for managing hyperlipidemia and associated metabolic disorders.